Structural analysis along the Ouray fault, southwestern Colorado: implications for the kinematic development of the late Paleozoic Ancestral Rocky Mountains - Johnson, Erinn P., author; Singleton, John, advisor; Sutton, Sally, committee member; Sharp, Julia, committee member (Colorado State University. Libraries, 2021)
The Ouray fault in southwest Colorado provides insight into the geometry and kinematics of deformation during the formation of the late Paleozoic Ancestral Rocky Mountains (ARM). The Ouray fault strikes WNW-ESE and dips subvertically to steeply south, juxtaposing the Paleoproterozoic Uncompahgre Group on the south side against Mississippian-Pennsylvanian strata on the north side. Kinematic data from the Ouray fault, adjacent small-scale faults, the observed offset, and folds in Paleozoic strata indicate that the Ouray fault records sinistral transpression. Using the average 15° W-plunging slickenlines from the principal slip plane, we estimate the total oblique sinistral displacement of the fault to be ~600 to 800 m. The uniformly overlapping Mesozoic strata atop the projected trace of the Ouray fault indicate that the fault is a preserved ARM structure not reactivated during the Laramide orogeny. The Ouray fault is oriented subparallel to the Uncompahgre Group bedding and follows the weaker Uncompahgre phyllite for most of its length, suggesting the preexisting structures within the Uncompahgre Group greatly influenced the orientation of the Ouray fault. N-S- to NW-SE-striking joints and quartz veins in all geologic units spanning the Paleoproterozoic to the Cenozoic postdate slip on the Ouray fault and likely formed during Cenozoic magmatism. A sample of calcite from the principal slip plane of the Ouray fault yielded a U-Pb date of 39.3 ± 6.2 Ma. I interpret this date to record resetting by late Eocene hydrothermal fluid flow. The record of strain around the Ouray fault may be representative of the southwestern margin of the Ancestral Uncompahgre uplift in Colorado. This study supports recent tectonic models for the ARM system which propose that ARM uplift was driven by NE-SW compression during the Pennsylvanian and Permian periods.
Zip file contains appendix and plates 1 and 2.
Keywords: kinematic analysis; Ouray fault; Uncompahgre uplift; mapping; Ancestral Rocky Mountains; sinistral transpression